Cystatin C protects neuronal cells from amyloid β-induced toxicity - Tizon, Belen (2010)
Multiple studies suggest that cystatin C (CysC) has a role in Alzheimer's disease (AD) and a decrease in CysC secretion is linked to the disease in patients with a polymorphism in the CysC gene. CysC binds amyloid β (Aβ) and inhibits formation of Aβ fibrils and oligomers both in vitro and in mouse models of amyloid deposition. Here we studied the effect of CysC on cultured primary hippocampal neurons and a neuronal cell line exposed to either oligomeric or fibrillar cytotoxic forms of Aβ. The extracellular addition of the secreted human CysC together with preformed either oligomeric or fibrillar Aβ increased cell survival. While CysC inhibits Aβ aggregation, it does not dissolve preformed Aβ fibrils or oligomers. Thus, CysC has multiple protective effects in AD, by preventing the formation of the toxic forms of Aβ and by direct protection of neuronal cells from Aβ toxicity. Therapeutic manipulation of CysC levels, resulting in slightly higher concentrations than physiological could protect neuronal cells from cell death in Alzheimer's disease.